Effectiveness of an Integrated Civic Education–Science Learning Model Using the Civic-Scientific Literacy Approach to Improve Science Process Skills in Junior High School Students - Elfahmi Lubis; Kasmiruddin Kasmiruddin; Desy Eka Citra Dewi (IJIS Edu : Indonesian Journal of Integrated Science Education, 2025)
This study examines the effect of an integrated Civic Education (PKn)-Science learning model on developing Science Process Skills (SPS) through a Civic-Scientific Literacy (CSL) approach in eighth-grade students. A non-equivalent pretest-posttest control group quasi-experimental design was applied to 64 students at SMP Negeri X Bengkulu. SPK data collection was conducted through tests, analyzed using ANCOVA, while CSL was evaluated using a rubric. The results showed that the integrated PKn-Science learning model significantly improved students' SPK (F=32.10, p<0.001, ηp2=0.347) compared to the control group. This model was also effective in facilitating the development of students' CSL, as evidenced by improvements in their ability to understand socio-scientific issues, evaluate evidence, engage in ethical-social reasoning, and participate in argumentation. A positive and significant correlation was also found between improvements in CSL and KPS (r=0.68, p<0.001), confirming the synergistic relationship between the two. This study concludes that integrating Civic Education and Science through the CSL approach is an effective strategy for fostering scientifically literate students and responsible citizens